2022
DOI: 10.1007/s40314-022-01844-z
|View full text |Cite
|
Sign up to set email alerts
|

Two-step peer methods with equation-dependent coefficients

Abstract: We introduce a new class of explicit two-step peer methods with the aim of improving the stability properties of already existing peer methods, by making use of coefficients depending on the Jacobian of the Ordinary Differential Equations (ODEs) system to solve. Numerical tests highlight the best stability and accuracy properties of the new methods compared to the classical and equation-dependent ones proposed in Conte et al. (Lect Notes Comput Sci 12949:309–324, 2021).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…We have solved it with the 4-stage peer methods deduced in the previous section, the DOPRI5 and the sixth-order Adams-Bashforth-Moulton (ABM6) to show the behaviour of this class of methods in high dimension problems. with the horizontal force F y (t) = 1/(cosh(4t − 2.5)) 4 and the vertical force F x (t) = 0.4. The initial conditions are θ l (0) = θ(0) = 0, the integration interval is [0, 3.723] and choosing n = 40 we obtain a system of ODEs of dimension 80.…”
Section: Klinge425mentioning
confidence: 99%
See 4 more Smart Citations
“…We have solved it with the 4-stage peer methods deduced in the previous section, the DOPRI5 and the sixth-order Adams-Bashforth-Moulton (ABM6) to show the behaviour of this class of methods in high dimension problems. with the horizontal force F y (t) = 1/(cosh(4t − 2.5)) 4 and the vertical force F x (t) = 0.4. The initial conditions are θ l (0) = θ(0) = 0, the integration interval is [0, 3.723] and choosing n = 40 we obtain a system of ODEs of dimension 80.…”
Section: Klinge425mentioning
confidence: 99%
“…where ⊗ denotes the standard Kronecker product and I m is the unit matrix of order m. For our studies of order and stability it will be sufficient to consider the scalar case (m = 1) in which (4) becomes (5) In general, two-step s-stage peer methods require s derivative function calls per step. Nevertheless, Horváth and coworkers [11] and Klinge and coworkers [12] have shown that if the matrices A, B and R have a special structure, it is possible to employ less function calls by re-using previously computed stages from the previous steps in the current one, in a similar way as Runge-Kutta schemes do with "first-same-as-last"(FSAL) technique [6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations